1501. Pragmatic Assessment of Influenza Vaccine Effectiveness in the DoD (PAIVED): Updates from Year 2 of multi-site trial. (31st December 2020) - Richard, Stephanie A; Burgess, Timothy; Burgess, Timothy; Collins, Limone; Colombo, Rhonda; Ganesan, Anuradha; Geaney, Casey; Hrncir, David; Lalani, Tahaniyat; Markelz, Ana E; Maves, Ryan C; McClenathan, Bruce; et al.
Abstract: Background: Despite nearly universal influenza vaccination for active duty military personnel, breakthrough influenza infections occur. We are reporting on the second year of the Pragmatic Assessment of Influenza Vaccine Effectiveness in the DoD (PAIVED), comparing three FDA-licensed influenza vaccine types (egg-based, cell -based, and recombinant) to assess differences in immunogenicity and effectiveness. Methods: Participants in the second year of PAIVED were enrolled from Oct 2019 through Jan 2020 at 9 military facilities. Participants received weekly inquiries about influenza-like-illnesses (ILI) experienced in the past week, and if the participant reported having a cough or sore throat and a) muscle/body aches or fatigue and/or b) being feverish or having chills, they were scheduled for a clinic visit. During this visit, a blood sample and a nasal swab were collected, as well as information about symptom duration and severity. A second (convalescent) visit was conducted approximately 4 weeks later, which involved collecting additional information about the duration of symptoms and illness burden, as well as a second blood draw. Due to the COVID-19 pandemic, acute and convalescent visits were disrupted at most sites in March and April due to COVID-19 precautions. Results: PAIVED year 2 enrolled 5, 892 participants who completed demographic forms (Table 1). Among those who reported any ILIs, most reported one ILI (1, 345), while 264 reported two ILIs, and 42 reported three ILIs. Nasal swabs were processed from 273 ILIs at four sites (Fig 1), and 14 cases of influenza were identified thus far. The median duration of ILIs was ten days, with a median of three days of limited activity, and two days with fever. Nine individuals were hospitalized. Table 1. Demographic characteristics of individuals enrolled in PAIVED 2019/20 Figure 1. Lab results as of 5/15 (N=273 samples) Conclusion: Over 25% of participants reported an ILI, and 5% of the nasal swabs that have been tested thus far have been positive for influenza. While most samples have not yet been analyzed, we have identified some breakthrough cases of influenza among vaccinated participants. Planned analyses include comparative vaccine effectiveness in order to inform future vaccine purchasing decisions. Disclaimer Disclosures: All Authors : No reported disclosures